Strategies for Lignin Pretreatment, Decomposition and Modification: A Review - Tolesa, Leta Deressa; Lee, Ming-Jer (Universitas Negeri Semarang, 2020)
The dependency of chemical industry on nonrenewable sources of energy such as petroleum based carbon feedstock is rising dramatically day to day. Nonetheless, global warming caused by greenhouse gas emissions threatens the environment balance and the climate stability. Accordingly, it is necessary to find a renewable resource to decrease the environmental concern, specifically gaseous emissions from fossil fuels and to provide the energy stock. Outstanding to the significance of lignocellulosic biomass as most remedy to the current environmental issues and substituent of nonrenewable source of energy, this review affords understandings about the role of lignin as polymer and raw material for large molecules. In this review article, types of lignin with their extraction methods, fractionation technology to valuable chemicals, modification of the macromolecules to other polymers with tunableproperties, and an extensive range of applications are discussed widely. The major valuable chemicals produced from lignin via chemical depolymerization are also summarized and illustrated with their molecular structures.